The Explanatory Power of Climate History for the 19th-Century Maritimes and Newfoundland: A Prospectus - Devor, Teresa (Acadiensis, 2014)
This article introduces the sources, methods, and groundwork for regional climate history. A reconstruction of 19th-century climate in Halifax, Charlottetown, St. John’s, and the waters of the Maritimes and Newfoundland contributes to understanding the ways that extreme seasonality and climatic variability influenced daily life in the region. Agriculture and transportation were significantly influenced by weather and climate while the experience of backland farmers also illustrates the conjuncture of class, marginal microclimates, poor soils, and human suffering. Despite high climatic variability during the century, the overall pattern is one of annual warming, which continued into the 20th century.